Slave captain : the career of James Irving in the Liverpool slave trade - Schwarz, Suzanne (Liverpool English texts and studies, 2008)
As few accounts written by slave ship captains are known to have survived, the personal papers of James Irving are of tremendous interest and academic significance. Irving built a successful career in the slave trade of eighteenth-century Liverpool, first as a ship?s surgeon and then as a captain. Remarkably he was himself enslaved when his ship was wrecked off the coast of Morocco and he was captured by people described as "wild Arabs" and "savages". This edition of forty letters and his journal reveals the reaction of the slaver to the experience of slavery, as well as throwing light on the